Interactions between Urban Form and Mobility: Comprehensive Meta-analysis of the Brazilian Context - Garrefa, Fernando; Souza, Aline Ribeiro; Joseph, Darla Kenyatha; Gonçalves, Gabriel de Lima; Freitas, Laiane Cristina de (National Journal of City Management, 2024)
This study analyzes the relationship between urban form and mobility in Brazil, considering its regional diversity. The study involved meta-analysis and structured literature review examining studies published between 2013 and 2023. The results highlight the importance of walkability and adequate infrastructure for the improvement of urban mobility, influencing quality of life and sustainability. Public policies adapted to local particularities are necessary to promote sustainable urban mobility. The study contributes with an interdisciplinary and quantitative approach in the analysis of the complex relationships between urban form and mobility, using bibliometric analysis to offer a new perspective on the subject.
Keywords: Urban form; Mobility; Walkability